Effects of experiences of pleasure and pathogenic suffering on the work of accounting professionals - Zonatto, Vinícius Costa da Silva; Lunardi, Micheli Aparecida; Degenhart, Larissa; Gonçalves, Bruna da Silva da Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study investigates experiences of pleasure and suffering in the work context of 365 professional accountants, evaluating their relationships and their effects on the performance of tasks. It also identifies coping strategies used to confront the experiences of suffering experienced. Descriptive research was carried out by means of a survey, with the application of quantitative and qualitative data analysis techniques. The results reveal that professional accountants are exposed to tensions in the organizational environment, which result in the appearance of experiences of pleasure and / or pathogenic suffering, resulting from the conditions of this environment, which influence, in some way, their attitudes, behaviors and performance at work. Accountant professionals respond differently to confront situations of suffering experienced, with planning and prioritizing work activities being the main coping strategies adopted.